Applicability of American College of Clinical Pharmacy (ACCP) competencies to clinical pharmacy practice in Egypt - Mahmoud A. Elmaaty; Ahmed A. Elberry; Raghda R. Hussein; Doaa M. Khalil; Amani E. Khalifa (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: The American College of Clinical Pharmacy (ACCP) prepared clinical pharmacist competencies that have specific recommendations. Recently, many efforts to advance clinical pharmacy services in Egypt exist. The literature revealed that no country has assessed the extent of applicability of ACCP competencies in its current pharmacy practice setting. Egyptian pharmacists can provide feedback about applicability of such competencies in clinical pharmacy settings in Egypt. Objective: The objective of this study was to investigate the extent to which ACCP competencies were implemented by Egyptian clinical pharmacists and therefore evaluate development of clinical pharmacy practice in Egypt. The study also investigated factors affecting the applicability of such competencies in the current clinical pharmacy practice setting in Egypt. Methods: Four hundred and ninety-five randomly selected clinical pharmacists from several hospitals were invited to participate in a cross sectional survey using a self-administered validated questionnaire composed of 31 questions classified into six domains. This questionnaire was designed to determine the pharmacists' perception about applicability of ACCP competencies to clinical pharmacy practice in Egypt. Results: The response rate was 64% as 317 out of 495 pharmacists completed the questionnaire. These pharmacists were categorized according to age; gender; qualifications; years of previous work experience, years since BSc. and type of hospitals they are currently working at. Analysis of data revealed the professionalism domain to have the highest percentage of acceptance among pharmacists, while the system-based care & population health domain had the lowest percentage of acceptance. Results also showed that qualifications of participants did not affect their response in three domains; "Direct Patient Care", "Systems-based Care & Population Health" and "Continuing Professional Development" (p=0.082, 0.081, 0.060), respectively. Nevertheless, qualifications of participants did affect their response in the other three domains; "Pharmacotherapy Knowledge", "Communication" and "Professionalism" (p<0.05). The age of pharmacists, gender, years of previous work experience, and graduation year did not affect their responses in all six domains. The type of hospital they are currently working at, though, affected their responses where, there was a highly statistically significant increase of the mean score of all domains among participants working at the NGOs/private hospitals compared to governmental hospitals (p<0.001). Conclusions: Egyptian pharmacists generally apply high percentage of ACCP competencies but the provided clinical pharmacy services need to be improved through applying the standards of best practice.